Comprehensive review of the traditional uses and the potential benefits of epimedium folium - Cui, Jialu; Lin, Lin; Hao, Feiran; Shi, Zhuo; Gao, Yehui; Yang, Tingyu; Yang, Chunqi; Wu, Xiangjun; Gao, Rong; Ru, Yi; Li, Fangyang; Xiao, Chengrong; et al. (Frontiers in Pharmacology, 2024)
ABSTRACT: Epimedium Folium has been extensively utilized for medicinal purposes in China for a significant period. This review undertakes a comprehensive examination of literature pertaining to Epimedium and its metabolites over the past decade, drawing from databases such as PubMed. Through meticulous organization and synthesis of pertinent research findings, including disease models, pharmacological effects, and related aspects, this narrative review sheds light on the principal pharmacological activities and associated mechanisms of Epimedium in safeguarding the reproductive system, promoting bone health, mitigating inflammation, and combating tumors and viral infections. Consequently, this review contributes to a more profound comprehension of the recent advances in Epimedium research.